2019
DOI: 10.3390/su11133682
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Metro Passenger Organizing of Alighting and Boarding Processes: Simulated Evidence from the Metro Station in Nanjing, China

Abstract: Since the long dwell time and chaotic crowds make metro trips inefficient and dissatisfying, the importance of optimizing alighting and boarding processes has become more prominent. This paper focuses on the adjustment of passenger organizing modes. Using field data from the metro station in Nanjing, China, a micro-simulation model of alighting and boarding processes based on an improved social force paradigm was built to simulate the movement of passengers under different passenger organizing modes. Unit flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…Wei Y used smart card data to propose the data filtering process and exception recognition, and classified and explained exceptions [49]. Yu J used the field data of the Nanjing metro stations to establish an improved social force model and simulate the efficiency of passengers under different organizational modes [50].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wei Y used smart card data to propose the data filtering process and exception recognition, and classified and explained exceptions [49]. Yu J used the field data of the Nanjing metro stations to establish an improved social force model and simulate the efficiency of passengers under different organizational modes [50].…”
Section: Introductionmentioning
confidence: 99%
“…Direction and stations of Nanjing metro lines 15,14,13,12,11,10,9,8,7,6,5,41,42,43,44,45,46,47,48,49,50,. 51, 52, 53, 54, 55] …”
mentioning
confidence: 99%
“…Yu et al. concluded that the separation of alighting and boarding can decrease the number of friction surfaces, improve the flow rate, and lower the average delay [22] . Therefore, this study investigates mitigation techniques for alighting and boarding passenger conflicts in subways, which considers the separated strategy of alighting and boarding for the bus system (one-way flow at any door).…”
Section: Methodologiesmentioning
confidence: 99%
“…The location dimension can be represented by the line, station, station type, and specific spot. The station type element contains the transfer station, terminal station, and normal station [59]. The specific spots include places such as carriages, platforms, gate machines, ladders, and tunnels.…”
Section: Scenario Analysis Of Metro Emergenciesmentioning
confidence: 99%